The Nutrient Profile of Foods Consumed Using the British Food Standards Agency Nutrient Profiling System Is Associated with Metabolic Syndrome in the SU.VI.MAX Cohort. Issue 10 (19th August 2015) - Julia, Chantal; Fézeu, Léopold K; Ducrot, Pauline; Méjean, Caroline; Péneau, Sandrine; Touvier, Mathilde; Hercberg, Serge; Kesse-Guyot, Emmanuelle
Abstract: Background: Metabolic syndrome (MetS), comprising high waist circumference, blood pressure, glycemia, and triglycerides, and lower HDL cholesterol could in part be prevented by adequate nutrition. Nutrient profiling systems could be useful public health tools to help consumers make healthier food choices. An individual dietary index (DI) based on nutrient profiling of foods consumed could characterize dietary patterns in relation to the onset of MetS. Objective: The objective of this study was to prospectively investigate the association between the Food Standards Agency (FSA) Nutrient Profiling System (NPS) DI and the onset of MetS in a middle-aged French cohort. Methods: Participants from the SUpplémentation en VItamines et Minéraux AntioXydants cohort (SU.VI.MAX, n = 3741) were included in the present study. The FSA NPS DI was computed by using dietary data from 24 h records at inclusion. MetS was identified at baseline and at year 13 of follow-up with the use of self-reported medication, data from clinical investigations, and biological measurements. A prospective association between the FSA NPS DI (in quartiles and continuous) and the onset of MetS was investigated by using logistic regression. Results: Poorer diets identified with the use of the FSA NPS DI were significantly associated with a higher risk of developing MetS (OR for poorer vs. healthier FSA NPS DI: 1.43; 95% CI: 1.08, 1.89; P -trend across quartiles = 0.02). The FSA NPS DI was significantly associated with the systolic blood pressure (SBP) and diastolic blood pressure (DBP) components of MetS (difference between healthier vs. poorer FSA NPS DI: 2.16 mm Hg for SBP and 1.5 mm Hg for DBP, P -trend across quartiles = 0.02). Conclusion: The FSA NPS DI was prospectively associated with the onset of MetS in a middle-aged French population. The application of NPSs in public health initiatives may help the population make healthier food choices, which might reduce the risk of developing MetS.